1977
DOI: 10.1126/science.841320
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned Narcotic Withdrawal in Humans

Abstract: Subjective and physiological manifestations of the narcotic withdrawal syndrome were produced as a conditioned response. Withdrawal reactions precipitated by the narcotic antagonist naloxone in methadone-dependent volunteers were the unconditioned response. These data support clinical anecdotes of withdrawal symptoms occurring in former addicts when they return to their drug-related environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(97 citation statements)
references
References 4 publications
4
92
0
1
Order By: Relevance
“…Thus, conditioning to a drug of abuse renders the conditioning context prone to a withdrawal response that is context-specific. Our results agree with the hypothesis proposed by several authors (25,(36)(37)(38)(39) that opiate withdrawal symptoms frequently reflect classically conditioned responses. Evidence of context-specific withdrawal exists in both humans and animals, and this conditioned withdrawal is believed to be an important factor that precipitates craving and relapse in abstinent ex-addicts (1,37,40).…”
Section: Discussionsupporting
confidence: 83%
“…Thus, conditioning to a drug of abuse renders the conditioning context prone to a withdrawal response that is context-specific. Our results agree with the hypothesis proposed by several authors (25,(36)(37)(38)(39) that opiate withdrawal symptoms frequently reflect classically conditioned responses. Evidence of context-specific withdrawal exists in both humans and animals, and this conditioned withdrawal is believed to be an important factor that precipitates craving and relapse in abstinent ex-addicts (1,37,40).…”
Section: Discussionsupporting
confidence: 83%
“…The presentation of drug-associated stimuli promotes drug seeking and relapse in addicts (Ehrman et al, 1992;Foltin and Haney, 2000;Heather et al, 1991;O'Brien et al, 1990;O'Brien et al, 1977). Thus, pharmacological manipulations that disrupt retrieval of long-term memories offer a particularly efficacious avenue for therapies targeting the elimination of these drug-associated memories.…”
Section: Time In Chamber (Sec)mentioning
confidence: 99%
“…Presentation of these cues can elicit craving in humans (Childress et al, 1986;Ehrman et al, 1992;Foltin and Haney, 2000;O'Brien et al, 1977) and stimulate active drug seeking in rodents (Banna et al, 2010;Chauvet et al, 2009;Fuchs et al, 2004;Mueller and Stewart, 2000). The associations between these cues and the drug reinforcer are acquired, consolidated, and readily retrieved in the presence of the cues.…”
Section: Introductionmentioning
confidence: 99%
“…Animal models showed that environmental cues associated with drug availability could provoke conditioned withdrawal symptoms and reinstatement of drug taking (Goldberg and Schuster, 1970). The Penn/VA human laboratory showed in human beings, for the first time, that opiate withdrawal symptoms (tearing of the eyes, runny nose, tachycardia, nausea, vomiting) and subjective craving for heroin could be produced as a conditioned response in the laboratory (O'Brien et al, 1977). One of the papers demonstrating this phenomenon was published in Science and consisted of training trials in which an odor was paired with a small dose of naloxone given to methadone-maintained volunteers.…”
Section: Addiction Is a Chronic Disease Of The Brainmentioning
confidence: 99%